Ferulic Acid Administered at Various Time Points Protects against Cerebral Infarction by Activating p38 MAPK/p90RSK/CREB/Bcl-2 Anti-Apoptotic Signaling in the Subacute Phase of Cerebral Ischemia-Reperfusion Injury in Rats - Cheng, Chin-Yi; Tang, Nou-Ying; Kao, Shung-Te; Hsieh, Ching-Liang (PLOS ONE, 2016)
Objectives This study aimed to evaluate the effects of ferulic acid (FA) administered at various time points before or after 30 min of middle cerebral artery occlusion (MCAo) followed by 7 d of reperfusion and to examine the involvement of mitogen-activated protein kinase (MAPK) signaling pathways in the cortical penumbra. Methods FA was intravenously administered to rats at a dose of 100 mg/kg 24 h before ischemia (B-FA), 2 h before ischemia (P-FA), immediately after ischemic insult (I-FA), 2 h after reperfusion (R-FA), or 24 h after reperfusion (D-FA). Results Our study results indicated that P-FA, I-FA, and R-FA effectively reduced cerebral infarct areas and neurological deficits. P-FA, I-FA, and R-FA significantly downregulated glial fibrillary acidic protein (GFAP), mitochondrial Bax, cytochrome c, and cleaved caspase-3 expression, and effectively restored the phospho-p38 MAPK (p-p38 MAPK)/p38 MAPK ratio, phospho-90 kDa ribosomal S6 kinase (p-p90RSK) expression, phospho-Bad (p-Bad) expression, the phospho-cAMP response element-binding protein (p-CREB)/CREB ratio, the cytosolic and mitochondrial Bcl-2/Bax ratios, and the cytosolic Bcl-xL/Bax ratio in the cortical penumbra 7 d after reperfusion. SB203580, a specific inhibitor of p38 MAPK, administered 30 min prior to ischemia abrogated the downregulating effects of I-FA on cerebral infarction, and mitochondrial Bax and cleaved caspase-3 expression, and the upregulating effects of I-FA on the p-p38 MAPK/p38 MAPK ratio, p-p90RSK expression, p-Bad expression, and the p-CREB/CREB, and cytosolic and mitochondrial Bcl-2/Bax ratios. Conclusions Our study results thus indicate that P-FA, I-FA, and R-FA effectively suppress reactive astrocytosis and exert neuroprotective effects against cerebral infarction by activating p38 MAPK signaling. The regulating effects of P-FA, I-FA, and R-FA on Bax-induced apoptosis result from activation of the p38 MAPK/p90RSK/CREB/Bcl-2 signaling pathway, and eventually contribute to inhibition of the cytochrome c-mediated caspase-3-dependent apoptotic pathway in the cortical penumbra 7 d after reperfusion.